The ProTides Boom. (9th May 2016) - Mehellou, Youcef
Abstract: The masking of nucleoside phosphate and phosphonate groups by an aryl motif and an amino acid ester, nowadays known as the 'ProTide' technology, has proven to be effective in the discovery of nucleotide therapeutics. Indeed, this technology, which was invented by Chris McGuigan in the early 1990s, has inspired the discovery of two FDA‐approved antiviral nucleotide drugs, and many more are currently undergoing (pre)clinical development. The usefulness of this technology in the discovery of nucleotide therapeutics is showcased in this Highlight by discussing the ProTides development and the various ProTides that have reached clinical trials. Abstract : Nucleotide therapeutics : The phosphate and phosphonate 'ProTide' technology, which was invented by the McGuigan lab in the early 1990s, has proven to be effective in the discovery of nucleotide therapeutics. Impressively, it has already inspired the discovery of two FDA‐approved drugs with many more in (pre)clinical development.